Quercetin/Zinc complex and stem cells: A new drug therapy to ameliorate glycometabolic control and pulmonary dysfunction in diabetes mellitus: Structural characterization and genetic studies - Refat, Moamen S. (PLoS One, 2021)
Medicinal uses and applications of metals and their complexes are of increasing clinical and commercial importance. The ligation behavior of quercetin (Q), which is a flavonoid, and its Zn (II) (Q/Zn) complex were studied and characterized based on elemental analysis, molar conductance, Fourier-transform infrared (FTIR) spectra, electronic spectra, proton nuclear magnetic resonance ((1)H-NMR), thermogravimetric analysis, and transmission electron microscopy (TEM). FTIR spectral data revealed that Q acts as a bidentate ligand (chelating ligand) through carbonyl C(4) = O oxygen and phenolic C(3)–OH oxygen in conjugation with Zn. Electronic, FTIR, and (1)H-NMR spectral data revealed that the Q/Zn complex has a distorted octahedral geometry, with the following chemical formula: [Zn(Q)(NO(3))(H(2)O)(2)].5H(2)O. Diabetes was induced by streptozotocin (STZ) injection. A total of 70 male albino rats were divided into seven groups: control, diabetic untreated group and diabetic groups treated with either MSCs and/or Q and/or Q/Zn or their combination. Serum insulin, glucose, C-peptide, glycosylated hemoglobin, lipid profile, and enzymatic and non-enzymatic antioxidant levels were determined. Pancreatic and lung histology and TEM for pancreatic tissues in addition to gene expression of both SOD and CAT in pulmonary tissues were evaluated. MSCs in combination with Q/Zn therapy exhibited potent protective effects against STZ induced hyperglycemia and suppressed oxidative stress, genotoxicity, glycometabolic disturbances, and structural alterations. Engrafted MSCs were found inside pancreatic tissue at the end of the experiment. In conclusion, Q/Zn with MSC therapy produced a synergistic effect against oxidative stress and genotoxicity and can be considered potential ameliorative therapy against diabetes with pulmonary dysfunction, which may benefit against COVID-19.